Analisis penerapan keselamatan dan kesehatan kerja (K3) pada pekerja lapangan PLN unit - Salsabilla Maulida; Budi Aswin; Usi Lanita; Fajrina Hidayati (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Backgroung: The implementation of Occupational Safety and Health (OHS) in the electricity sector is crucial given the high occupational risks. The PLN Unit, which operates a 100 MW gas-fired power plant, employs 14 field workers exposed to various potential hazards. Initial observations indicate a gap between the applicable OHS policy and the practice of using PPE in the field. Purpose: To describe the implementation of OHS among field workers at the PLN Unit, covering aspects of occupational health (weather and physical-mental conditions) and occupational safety (people, supervision, and equipment availability). Method: Qualitative research with a descriptive design was conducted from August 2025 to March 2026 at the PLN Payo Selincah Unit with six purposively selected informants. Data were collected through in-depth interviews, observation, and documentation. Analysis used the Miles and Huberman model, supported by NVivo software. Results: Institutionally, OHS has been well-implemented, supported by the OHS Management System (SMK3) policy, the Zero Accident Award, IP-Safe, annual PPE replacement, JSA (Workplace Safety Assessment), LOTO (Lotto of Action), and emergency response simulations. However, critical challenges in the field include inconsistent use of PPE during emergencies, limited OHS personnel, suboptimal leadership exemplars, and workload pressures that impact OHS compliance. Conclusion: OHS implementation at PLN Units is quite good institutionally but requires strengthening leadership exemplary behavior, additional OHS personnel, emergency PPE protocols, technical solutions for cramped engine rooms, and a sustainable OHS culture program to foster compliance through self-awareness. Keywords: Occupational Health And Safety; Field Workers; PLN; Safety Culture; PPE Compliance